2018
DOI: 10.1590/1678-4162-9498
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse elastography of the eyes of brachycephalic dogs

Abstract: Eyes from brachycephalic dogs were studied by acoustic radiation force impulse (ARFI) elastography to establish quantitative and qualitative reference values related to the shape and rigidity of some ocular structures. Eighty-four eyes from 42 adult brachycephalic dogs were included in this study. Animals were subjected to physical, laboratory, and ophthalmic examinations. Following confirmation of good health, the dogs were subjected to ultrasonography and ARFI elastography, emphasizing the optic nerve, cilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…After the qualitative analysis, three regions of interest, covering the entire length of the lens both in the cortex and in the nucleus were defined by positioning the caliper over these areas. Using this methodology, the software automatically calculates the shear wave velocity (SWV) in m/s of each region and the mean of which was calculated for statistical analysis (Abreu et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the qualitative analysis, three regions of interest, covering the entire length of the lens both in the cortex and in the nucleus were defined by positioning the caliper over these areas. Using this methodology, the software automatically calculates the shear wave velocity (SWV) in m/s of each region and the mean of which was calculated for statistical analysis (Abreu et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In general, more rigid tissues suffer less deformity and after cessation of the applied force, the tissue returns to its original shape. This technique is performed in real-time, non-invasively, and more often does not require sedatives or anesthetics (Carvalho et al 2015, Abreu et al 2018. Currently there is no study that uses the elastography for the diagnosis of cataracts in animals or humans.…”
Section: Introductionmentioning
confidence: 99%
“…The same study observed high rigidity in lenticular capsules, shown in dark grey (Figure 3). ARFI elastography also showed loss of mosaic patterns in dogs with different degrees of cataract ( Figure 4) (ABREU et al, 2018). , showing lens, ciliary body, vitreous humor (A and B) and fundus of eye (C and D), of eye of the Shih Tzu dog breed.…”
Section: Elastographymentioning
confidence: 97%
“…Ultrasonographic measurements are within known normality standards, although there is no variety of studies other than brachycephalic (Kobashigawa et al, 2015;Abreu et al, 2018).…”
Section: Arqmentioning
confidence: 99%